2019
DOI: 10.1002/jgm.3128
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic significance of serum miRNA‐146‐a expression in Egyptian children with sepsis in a pediatric intensive care unit

Abstract: Background: Previous studies have suggested a strong genetic effect on sepsis pathogenesis. The present study aimed to investigate the role of miRNA-146-a expression in pediatric sepsis. Methods:The study included 55 pediatric sepsis patients and 60 control children of the same age and sex. Serum miRNA-146-a expression was measured using a quantitative real-time polymerase chain reaction. C-reactive protein, interleukin-6, tumor necrosis factor-α and procalcitonin levels were measured by an enzymelinked immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Risk of bias is mainly derived from the index test. The conduct or interpretation of the index test introduced high risk in 6 records [ 7 , 8 , 17 , 19 , 23 , 28 ] and unclear risk in 13 articles [ 6 , 14 – 16 , 18 , 20 , 21 , 25 27 , 29 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk of bias is mainly derived from the index test. The conduct or interpretation of the index test introduced high risk in 6 records [ 7 , 8 , 17 , 19 , 23 , 28 ] and unclear risk in 13 articles [ 6 , 14 – 16 , 18 , 20 , 21 , 25 27 , 29 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Current literature suggested miRNAs played a vital role in the pathophysiology of sepsis and could distinguish the various phases of sepsis [ 6 9 , 11 , 14 – 31 ]. Several miRNAs, such as miR-146-a, miR-125b, and miR-223, were positively or negatively associated with sepsis severity [ 22 , 25 , 28 ]. In this present study, the AUC of miRNAs was 0.89 (0.86–0.92), which is higher than that of PCT [0.74 (0.70–0.77)] and CRP [0.77 (0.73–0.81)].…”
Section: Discussionmentioning
confidence: 99%
“…Our search on deregulated miRNAs in sepsis resulted in seven studies with significant and consistent downregulation of miR-146a in peripheral blood. Karam et al examined circulating miR-146a levels in septic children compared to age and gender matched HCs (Karam et al 2019). The serum levels of miR-146a were significantly decreased in sepsis, with an even stronger signal in septic shock and correlated with survival.…”
Section: Mir-146a and Sepsismentioning
confidence: 99%
“…The emerging studies regarding NS have substantially improved the understanding of the pathology of the disease and revealed the diagnostic and treatment potentials of different biological factors in the progression of NS. Of which, microRNAs (miRs) have elicited lots of interest of scientists and clinicians for their involvement in sepsis [5][6][7][8][9]. MiRs are a class of endogenous and non-coding short RNA molecules (~22 nt).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the roles of miRs in the development of sepsis, the study by Li et al indicated that miR-25 was involved in the treatment of ginkgolide A against sepsis [10] and the study by Zhang et al showed that miR-22-3p could serve as an early diagnostic biomarker for sepsis in clinic [11]. Moreover, miRs such as miR-146a, miR-574-5p, miR-122, and miR-133a have been reported to have reference value for the clinical diagnosis and prognosis of sepsis [5][6][7][8][9]. However, even with the evident interaction between sepsis and miRs, few studies have paid attention to the involvement of miRs in the development and treatment of NS.…”
Section: Introductionmentioning
confidence: 99%